2010
DOI: 10.1103/physreva.82.033407
|View full text |Cite
|
Sign up to set email alerts
|

Calculated Hanle transmission and absorption spectra of theRb87D1line with residual magnetic field

Abstract: This paper reports a theoretical study on the transmission spectra of an arbitrarily polarized laser beam through a rubidium cell with or without a buffer gas in Hanle-type coherent population trapping (CPT). This study examined how laser polarization, transverse magnetic field, and collisions with buffer gas affects the spectrum. The transmission spectrum due to CPT and the absorption spectrum due to the level crossing absorption (LCA) were calculated according to the laser polarization. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…They proposed that the enhanced absorption depends on both the TMF strength, and atom-laser interaction time, which increases due to the diffusive motion of Rb atoms in the presence of buffer gas atoms. Similar results were also obtained by Noh and moon [16]. They also varied the direction of the TMF in the plane perpendicular to the scanning magnetic field direction and found that the enhanced absorption observed at circularly polarized light is insensitive to the orientation of the TMF.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…They proposed that the enhanced absorption depends on both the TMF strength, and atom-laser interaction time, which increases due to the diffusive motion of Rb atoms in the presence of buffer gas atoms. Similar results were also obtained by Noh and moon [16]. They also varied the direction of the TMF in the plane perpendicular to the scanning magnetic field direction and found that the enhanced absorption observed at circularly polarized light is insensitive to the orientation of the TMF.…”
Section: Introductionsupporting
confidence: 84%
“…All the results obtained so far were computed by including collisional effects. The presence of collisions reinforces the population redistribution in the Zeeman sublevels due to the TMF [15][16][17]. When the atomic transit time ( ) T 1 γ ∝ γ is reduced to ∼0.03 ms (corresponding to a pure gas cell i.e.…”
Section: Effect Of Collisionsmentioning
confidence: 94%
See 1 more Smart Citation
“…As first observed by Zeeman in 1896 [5], the energy levels and transition probabilities of an atomic ensemble are extremely sensitive to an external magnetic field. Therefore a theoretical model for the absorption and dispersive properties of such ensembles has found utility in many applications, for example, Faraday dichroic beam splitter for Raman light [6]; Gigahertz-bandwidth atomic probes [7]; Hanletype coherent population trapping [8]; off-resonance laser frequency stabilization [9]; realizing narrowband atomic filters [10]; cooperative effects in an atomic nanolayer [11]; imaging microwave fields in vapour cells [12] and achieving a compact optical isolator [13].…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetically induced transparency or absorption effects are usually observed in atomic vapors as subnatural-width resonances either in a single-frequency magneto-optical (Hanle) configuration [43,44] or in a two-frequency light field [45,46]. Sign of the resonance (EIT or EIA) depends on different conditions of the experiment, such as a structure of involved energy levels in combination with light wave polarization and direction of magnetic field scan or presence of a residual magnetic field (in the Hanle configuration) [22,[46][47][48][49][50][51], collisional depolarization of the excited state in buffered or antirelaxation-coated vapor cells [48,[52][53][54] and others.…”
Section: Theorymentioning
confidence: 99%